2002
DOI: 10.1108/00483480210422750
|View full text |Cite
|
Sign up to set email alerts
|

Team responsibility structure and team performance

Abstract: The purpose is to analyse the impact of team responsibility (the division of job regulation tasks between team leader and team members) on team performance. It bases an analysis on 36 case studies in The Netherlands which are known to have implemented team-based work. The case studies were executed in 1997 by means of face-to-face interviews with HRM staff and line management. It concludes from the analyses that two different types of team responsibility prevail. In a``hierarchical team'' team leaders take res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…In most of the articles, teamwork was based on the delegation of responsibilities to employees and decentralized decision‐making. While some of the studies in our review are based on sociotechnical or work design theory, thus emphasizing teamwork and task design as the direct predictors of performance, others take strategic HRM theory as their starting point, defining teamwork or employee participation as one item in a list of possible ‘innovative work practices’ that can be introduced to enhance the ability of the human resources in organizations to contribute to organizational performance (Doorewaard et al 2002).…”
Section: Scope and Methodsmentioning
confidence: 99%
“…In most of the articles, teamwork was based on the delegation of responsibilities to employees and decentralized decision‐making. While some of the studies in our review are based on sociotechnical or work design theory, thus emphasizing teamwork and task design as the direct predictors of performance, others take strategic HRM theory as their starting point, defining teamwork or employee participation as one item in a list of possible ‘innovative work practices’ that can be introduced to enhance the ability of the human resources in organizations to contribute to organizational performance (Doorewaard et al 2002).…”
Section: Scope and Methodsmentioning
confidence: 99%
“…This way, teams can maximize the organization's resources because each team's unique resources flow across team boundaries so they can be used by their counterpart teams (Doorewaard, Van Hootegem, & Huys, 2002;Michalisin, Karau, & Tangpong, 2004). For example, organizational learning research emphasizes that accumulating organizational knowledge clearly depends on flow of resources, such as information across team boundaries (Sole & Edmondson, 2002).…”
Section: Outcomes Of Boundary Activitymentioning
confidence: 98%
“…Having control over the procedure used to make decisions (process control) and/or having control over the nature of the decision (decision control) appear to be important determinants to how subordinates relate to their leader and their efforts to secure a certain level of team performance. For example, past research has found that subordinates that are allowed little process and decision control over decisions are less satisfied with their superiors (Peterson, 1997;Phillips et al, 2001), and eventually perform worse (Doorewaard et al, 2002). In contrast, when subordinates are allowed to voice their opinions and take decisions, they are more satisfied with their leader.…”
mentioning
confidence: 94%